Sub-National Diplomacy Strategy: South Sulawesi & Ehime Prefecture Opportunities and Challenges Study - Febriansyah, Ahady; Rahman, Ishaq; Abdullah, Nurjannah; Hastira, Muhammad Fajhriyadi (AEGIS : Journal of International Relations, 2025)
This research analyzes the paradiplomacy strategy between South Sulawesi Province, Indonesia, and Ehime Prefecture, Japan, within the framework of sister-province cooperation. Paradiplomacy is an essential tool for local governments to strengthen international relations, especially in the fields of economy, education, and culture. This qualitative research uses a descriptive-analytical approach, using document analysis in the form of books, official reports of the South Sulawesi and Ehime governments, journals, newspapers, online sources, and relevant reports. In addition, face-to-face interviews were conducted with key stakeholders, including analysts from the Government and Regional Autonomy Bureau and translators from the South Sulawesi Cooperation Section. The findings highlight significant potential in fisheries, agriculture, and human resource development. However, challenges such as leadership transition, budget constraints, and communication barriers hinder implementation. The study emphasizes the importance of strategic planning and political commitment to improve the effectiveness of international sub-national cooperation.